Environment-dependent and anion-vacancy-controlled reversible phase transition of MoS2 synthesized by chemical vapor deposition. (20th July 2018) - Lee, Hyangsook; Cho, Yeonchoo; Kim, Un Jeong; Chung, Jaegwan; Yun, Dongjin; Kim, Hoijoon; Lee, Eunha; Kim, Hyoungsub
Abstract: The crucial role of anion vacancies on the phase stability of synthetic metal chalcogenides was elucidated by demonstrating the environment-dependent, reversible phase transition (2H ↔ 1T/1T′) of the MoS2 films synthesized by chemical vapor deposition. The origins of the sulfur (S)-vacancy-controlled phase transition of the synthetic MoS2 films were supported by various transmission electron microscopy (TEM) studies as well as density functional theory calculations. Under high-vacuum conditions, transition to the metastable 1T/1T′ phases was induced by weak electron irradiation during a TEM observation and explained by the detachment of molecules chemisorbed on the S-vacancy sites, and the subsequent electron-delocalization (charge-transfer) process. In addition, a spontaneous backward transition to a 2H phase could be triggered by exposing the sample to air, which induced electron localization by re-adsorption of ambient molecules on the S-vacancy sites.